One-step strategy for efficient Cr(VI) removal via phytate modified zero-valent iron: Accelerated electron transfer and enhanced coordination effect - Gan, Rui; Ye, Yuxuan; Zhan, Ziyi; Zhang, Qiuyue; Deng, Yuwei; Liu, Yingjie; Li, Haochen; Wan, Jun; Pei, Xuanyuan; Li, Qiang; Pan, Fei (Journal of hazardous materials, 2024)
The toxic Cr(VI) from industrial wastewater pose serious threat to the human beings and eco-systems. To reduce the operation processes and enhance the removal efficiency of Cr(VI), targeted design of functionalized material is critical in practical applications. Herein, we developed a one-step strategy for simultaneous Cr(VI) reduction and total Cr capture by a novel phytate modified zero-valent iron (PA-ZVI). The reaction kinetics of Cr(VI) removal by PA-ZVI (0.2225 min−1) was 53 times higher compared to ZVI (0.0042 min−1). The Fe(0) content on the surface of PA-ZVI increased from 2.2% to 15.6% compared to ZVI. Meanwhile, Cr(VI) was liable to adsorb on the surface of PA-ZVI due to its lower adsorption energy compared with the original ZVI (−2.09 eV vs −0.85 eV). The incorporation of the phytate ligand promoted electron transfer from iron core to Cr(VI), leading to the rapid in-situ reduction of Cr(VI) adsorbed on the surface of PA-ZVI to Cr(III). PA-ZVI exhibited a satisfactory performance for Cr(VI) removal at a broad pH range (3−11) and in the presence of coexisting ions and humic acid. Moreover, the reactor with the addition of PA-ZVI achieved more than 90% Cr(VI) removal within 72 h in continuous flow experiments. The feasibility of PA-ZVI for the removal of Cr(VI) is also validated in authentic wastewater. This work provides novel ZVI materials that can effectively address decontamination challenges from Cr(VI) pollution. [Display omitted] •Apparent rate constants k (min−1) of Cr (VI) removal by PA-ZVI was 53 times that of ZVI.•The increased surface Fe (0) content on PA-ZVI facilitated Cr (VI) removal.•Phytates favored the coordination effect and accelerated the electron transfer of ZVI.•PA-ZVI showed satisfactory performance toward Cr(VI) in authentic water matrices.